Aging during COVID-19 in Germany: a longitudinal analysis of psychosocial adaptation - Schlomann, Anna; Bünning, Mareike; Hipp, Lena; Wahl, Hans-Werner (European journal of ageing, 2022)
Existing theories of aging suggest that there may be similarities and differences in how COVID-19 impacts older people’s psychosocial adaptation compared to younger age groups, particularly middle-aged individuals. To assess the degree to which these impacts vary, we analyzed data from 3098 participants between the ages of 40 and 79 from an online survey in Germany. Data were collected at three measurement occasions between the start of the nationwide lockdown in mid-March 2020 and the end of the lockdown in early August 2020. The survey focused on everyday experiences during the COVID-19 crisis and collected various satisfaction ratings (e.g., general life satisfaction, satisfaction with family life, satisfaction with social contacts). At baseline, participants also provided retrospective ratings of satisfaction for the period before the COVID-19 crisis. In our analyses, we compared satisfaction ratings of middle-aged (40-64 years) and older individuals (65-79 years) and found that both middle-aged and older participants experienced the greatest decreases in satisfaction with social contacts, with more pronounced decreases seen in middle-aged participants. A similar pattern was observed for general life satisfaction, but the overall decreases were less pronounced in both groups compared to the decreases in satisfaction with social contacts. We also observed a partial recovery effect in all measures at the last measurement occasion, and this effect was more pronounced in older adults. Findings were also confirmed using age as a continuous variable and checking for linear and nonlinear effects of outcomes across the age range. Although ageism arose during the pandemic in the sense that older adults were labeled as a “risk group,” particularly at the start of the outbreak, we found consistently with other studies that middle-aged adults’ satisfaction decreased to a greater extent than that of older adults.